Parental leave benefits, household labor supply, and children's long-run outcomes - Rita Ginja; Jenny Jans; Arizo Karimi (Institute for Fiscal Studies (IFS), 2018)
We study how parental leave benefit levels affect household labor supply, family income, and child outcomes, exploiting the Speed Premium (SP) in the Swedish leave system. The SP grants mothers higher benefits for a subsequent child without re-establishing eligibility through market work, if two births occur within a pre-specified interval. We use the spacing eligibility cutoffs in a Regression Discontinuity framework and find that the SP improves educational outcomes of the older child, but not of the younger. Impacts are likely driven by increased maternal time and the quality of maternal time relative to the counterfactual mode of care.
Keywords: 330